Modernist dreams and green sagas: The neoliberal politics of Iceland's renewable energy economy. (December 2018) - Guðmundsdóttir, Hrönn; Carton, Wim; Busch, Henner; Ramasar, Vasna
Transitioning to renewable energy is an imperative to help mitigate climate change, but such transitions are inevitably embedded in broader socio-ecological and political dynamics. Recent scholarship has focused on these more-than-technological dimensions of energy transitions to help understand their promises and drawbacks. This article contributes to this research agenda by highlighting the importance of considering not only who benefits from renewable energy development, but also what renewable energy is for . We analyse two cases in Iceland, the Kárahnjúkar hydropower project and Hellisheiði geothermal energy plant, in which renewable energy was used to attract heavy industry investments in the form of aluminium smelters. Attractive regulatory conditions in the form of 'minimal red tape', low electricity prices and an industry-friendly tax regime led to significant profits for the aluminium industry but questionable benefits for the state and the people of Iceland. Renewable energy development in this way put Iceland's nature to use for private gain, while marginalizing alternative ideas of what that nature is for. Our analysis underlines the need to pursue perspectives that recognize the complex political and socio-ecological nature of energy systems, which includes attention to the political economy of industrial energy consumption.